Basic and advanced bayesian structural equation modeling : with applications in the medical and behavioural sciences - Song, Xin-Yuan.; Lee, Sik-Yum. (Hoboken : Wiley, 2012)
'This book introduces the Bayesian approach to SEMs, including the selection of prior distributions and data augmentation, and offers an overview of the subject's recent advances'--
Includes bibliographical references and index.
Keywords: Structural equation modeling; Bayesian statistical decision theory